The Needs Analysis of English in Bina Informatika Vocational High School of Bintaro as A Basis to Design English Teaching Materials - Albiansyah Albiansyah; Minkhatunnakhriyah Minkhatunnakhriyah (research, training and philanthropy institution Natural Aceh, 2021)
Abstract: This study aims to find out the need analysis of teaching and learning English for vocational high school students. It is focused on the students’ needs, deficiencies, and desires. To find the source of knowledge to design proper English materials, this study was performed at one of Bina Informatika vocational high school of bintaro , Tangerang Selatan. A series of questionnaires were distributed to multimedia students to analyze their needs, shortcomings, and motivation to learn English for vocational purposes. This survey research using a series of questionnaires covering three measures to determine the needs of students for particular purposes on materials in learning English. There were 41 participants in this study involving the eleventh graders. In figuring out the majority decisions for each item asked, the data were evaluated quantitatively. In investigating the reasons for each result, open-ended interviews were conducted with both the teacher and the students. The result showed that the students were supposed to be able to use English for everyday contact that would be beneficial to their future jobs since fluency in speaking and grammar were burdening them. Therefore, these students need contextual teaching on the delivered topics. In conclusion, the results of this research can be a landmark for creating a package of materials in English learning for the students. Abstrak: Penelitian ini bertujuan untuk mengetahui analisis kebutuhan pembelajaran bahasa Inggris bagi siswa SMK. Hal ini difokuskan pada kebutuhan, kekurangan, dan keinginan siswa yang menjadi sasaran pembelajaran. Untuk mengetahui sumber pengetahuan dalam merancang materi bahasa Inggris yang tepat, penelitian ini dilakukan di SMK Bina Informatika di Bintaro, Tangerang Selatan. Serangkaian kuesioner dibagikan kepada siswa multimedia untuk menganalisis kebutuhan, kekurangan, dan motivasi belajar bahasa Inggris untuk keperluan vokasional. Penelitian survei ini menggunakan serangkaian kuesioner yang mencakup tiga langkah untuk mengetahui kebutuhan siswa akan tujuan tertentu pada materi dalam pembelajaran bahasa Inggris. Ada 41 peserta dalam penelitian ini yang melibatkan siswa kelas sebelas. Dalam menentukan keputusan mayoritas untuk setiap item yang ditanyakan, data dievaluasi secara kuantitatif. Dalam menyelidiki alasan untuk setiap hasil, wawancara terbuka dilakukan dengan guru dan siswa. Hasil penelitian menunjukkan bahwa siswa diharapkan dapat menggunakan bahasa Inggris untuk percakapan sehari-hari yang akan bermanfaat bagi pekerjaan mereka di masa depan karena kefasihan berbicara dan tata bahasa membebani mereka. Oleh karena itu, para siswa ini membutuhkan pengajaran kontekstual pada topik yang disampaikan. Kesimpulannya, hasil penelitian ini dapat menjadi tonggak pembuatan bahan ajar bahasa Inggris bagi siswa.